2022
DOI: 10.3846/tede.2022.16575
|View full text |Cite
|
Sign up to set email alerts
|

Environ-Economic Balance Analysis in Bilateral Industrial Trade: A Comparison Between Australia and China

Abstract: Exchanges of products and services in bilateral industries may be accompanied by environmental and economic inequalities which lead to imbalanced situations in relation to environmental protection and economic development. In a close trade relationship between two countries such as Australia and China, their industries inevitably affect each other. This study maps the embodied CO2 emissions and value added in bilateral trade under the input–output model and measures the unequal exchanges in such trade using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…An empirical study has also proved that the countries with a low degree of participation in GVC experienced a great many difficulties in the reduction of emissions in the short to medium term (Wang et al, 2019). An industrial environ-economic balance index can be adopted to estimate the situation of two countries in bilateral trade based on the value added and environmental indicators (Gao et al, 2022). A similar finding shows that the high degree of GVC participation facilitates the transfer of carbon emission within the trade and brings a negative influence on activities of carbon reduction (Zhong et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 89%
“…An empirical study has also proved that the countries with a low degree of participation in GVC experienced a great many difficulties in the reduction of emissions in the short to medium term (Wang et al, 2019). An industrial environ-economic balance index can be adopted to estimate the situation of two countries in bilateral trade based on the value added and environmental indicators (Gao et al, 2022). A similar finding shows that the high degree of GVC participation facilitates the transfer of carbon emission within the trade and brings a negative influence on activities of carbon reduction (Zhong et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 89%
“…Jayanthakumaran and Liu (2016), for example, suggested that the bilateral trade between Australia and China plays an important role in lowering global CO 2 emissions and that both countries should adopt measures to avoid future border-price adjustment by reaching consensus on a sustainable trading scheme. However, a bilateral input-output model does not reveal the complex relationship between multi-regional economic activities and environmental pollution (Gao et al, 2022). With the development of international production networks, MRIO analysis has been introduced in order to draw a comprehensive picture of embodied CO 2 transfer amongst participants in global production chains.…”
Section: Literature Reviewmentioning
confidence: 99%